Liquid‐phase exfoliation of violet phosphorus for electronic applications. (1st June 2021) - Lin, Shenghuang; Lai, Wai Kin; Li, Yanyong; Lu, Wei; Bai, Gongxun; Lau, Shu Ping
Abstract: Large‐scale production of two‐dimensional (2D) materials still is a crucial point toward its practical applications. Violet phosphorus (VP) with a wide bandgap accelerates and broadens the potential applications of elemental phosphorus in optoelectronics. Here, we demonstrate the scalable production of solution‐processable violet phosphorus flakes stably dispersed in several solvents. The exfoliated VP flakes exhibit thickness‐dependent visible photoluminescence characteristics, which covers the shortcoming of black phosphorus. Meanwhile, the VP‐based field‐effect transistor reveals relatively competitive electrical properties to other liquid‐phase exfoliated 2D materials. Our study paves the way for a wide range of applications of optical devices, energy storage, catalysis, and sodium batteries based on large‐scale VP flakes. Abstract : Large‐scale production of two‐dimensional (2D) materials still is a crucial point toward its practical applications. Violet phosphorus (VP) with a wide bandgap accelerates and broadens the potential applications of elemental phosphorus in optoelectronics. Here, we demonstrate the scalable production of solution‐processable VP flakes stably dispersed in several solvents. The VP‐based field‐effect transistor reveals relatively competitive electrical properties to other liquid‐phase exfoliated 2D materials.